A COGNITIVE APPROACH TO THE HERMENEUTICS OF JONATHAN EDWARDS’S SERMONS - Choiński, Michał (Jonathan Edwards studies, 2014)
The author of the article employs cognitive poetics to investigate the language of Jonathan Edwards's sermons. The cognitive methodology seems particularly useful in the analysis of Edwards's preaching rhetoric because on the one hand, it puts emphasis on various stylistic mechanisms employed in the sermon, and, on the other hand, it stresses the role of context, thus helping in understanding the process of their reception. The author presents cognitive analyses of two sermons by Edwards: Future Punishment of the Wicked and Sinners in the Hands of an Angry God - in case of the former text, the imagery of the sermon is the focus of the study, in case of the latter, the emphasis is placed on the deictic shift mechanism.